An Open‐Label Study Investigating the 5‐HT 2A Receptor Occupancy of Remlifanserin (ACP‐204) With the PET Radioligand [ 18 F]Altanserin in Healthy Male Participants - Ethan S. Burstein; Christine Sandiego; Brian Raether; Xiaoshu Feng; Bryan Dirks; Mona Darwish; Peter Zhang; David S. Russell; Eugenii A. Rabiner; Sanjeev Pathak (Clinical Pharmacology in Drug Development, 2026)
Abstract Remlifanserin (ACP‐204) is a selective 5‐HT 2A receptor inverse agonist that builds upon scientific findings of its structural analog, pimavanserin. This Phase 1, open‐label study in healthy adults (N = 16) describes the central 5‐HT 2A receptor occupancy of remlifanserin at different doses and plasma concentrations using positron emission tomography imaging and radioligand [ 18 F]altanserin, with pimavanserin as a reference molecule. Receptor occupancy measurements taken at time to maximum plasma concentration (T max ) and various intervals up to five half‐lives after T max were correlated with study drug plasma concentrations and estimated from a Lassen plot. Administration of remlifanserin or pimavanserin resulted in plasma‐concentration‐dependent occupancy of 5‐HT 2A receptors (ranges, 53%–100% and 41%–100%, respectively) and was adequately predicted by an E max model with a fixed Hill slope of 1. The half maximal effective plasma concentration (EC 50 ) values for remlifanserin and pimavanserin were estimated to be 0.37 and 0.55 ng/mL, respectively, suggesting that remlifanserin occupies 5‐HT 2A receptors with comparable to slightly greater potency than pimavanserin. Single doses of remlifanserin were safe and well tolerated. Study findings will inform the development and dosing of remlifanserin in future Phase 2/3 trials.